Espumação química de PVC rígido empregando azodicarbonamida e bicarbonato de sódio - Gouvêa, Noélle Barbosa Favero (Universidade Federal de São Carlos, 2026)
Poly(vinyl chloride) (PVC) ranks third in the global production of thermoplastic polymers, and due to its long degradation time, it becomes essential to adopt strategies that reduce raw-material consumption in large-scale applications such as rigid sewer pipes. This study evaluated the chemical foaming of typical PVC formulations for sewage systems, comparing azodicarbonamide (pure and modified) and sodium bicarbonates, which present distinct decomposition kinetics, through incorporation in a torque rheometer and analyses of density, thermal characterization (TGA and DSC), scanning electron microscopy (SEM), mechanical testing, and compliance with technical standards. The results indicated that azodicarbonamide produced smaller and more uniform cells, with higher cell density, which translated into improved morphological control and greater expansion efficiency, particularly for the blowing agents Planagem CS-4M (10.5% expansion at 1.0 phr and 7.8% in manufactured pipes) and Planagem B-8 (4.3% at 1.0 phr and 2.9% in pipes). Sodium bicarbonates, although the most environmentally attractive option, generated more heterogeneous cells and yielded very low or null expansion (AO-653 with 1.0% and AO-421 with negative values), evidencing processing instability. Thermal and rheological analyses showed that the type of blowing agent influences the PVC crosslinking time, with azodicarbonamide accelerating the reaction while bicarbonates retard it, without altering the molar mass or the polymer’s thermal transitions, as confirmed by the K-value and DSC measurements. Overall, the morphological, thermal, and regulatory assessments demonstrated that azodicarbonamide-based systems are more suitable for rationalizing PVC consumption, combining significant expansion, thermal stability, and technical compliance, whereas sodium bicarbonates exhibited relevant limitations under the evaluated conditions.
Chemical foaming of rigid PVC using azodicarbonamide and sodium bicarbonate
Keywords: Poli (cloreto de vinila); Azodicarbonamida; Bicarbonato de sódio; Expansão química; Poly (vinyl chloride); Azodicarbonamide; Sodium bicarbonate; Chemical expansion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::INSTALACOES E EQUIPAMENTOS METALURGICOS; 9. Indústria, Inovação e Infraestrutura; 11. Cidades e Comunidades Sustentáveis; 12. Consumo e Produção Responsáveis